Navigating power in conservation - Shackleton, R.T.; Walters, G.; Bluwstein, J.; Djoudi, H.; Fritz, L.; Lafaye de Micheaux, F.; Loloum, T.; Nguyen, V.T.H.; Rann Andriamahefazafy, M.; Sithole, S.S.; Kull, C.A. (Wiley, 2023)
Conservation research and practice are increasingly engaging with people and drawing on social sciences to improve environmental governance. In doing so, conservation engages with power in many ways, often implicitly. Conservation scientists and practitioners exercise power when dealing with species, people and the environment, and increasingly they are trying to address power relations to ensure effective conservation outcomes (guiding decision-making, understanding conflict, ensuring just policy and management outcomes). However, engagement with power in conservation is often limited or misguided. To address challenges associated with power in conservation, we introduce the four dominant approaches to analyzing power to conservation scientists and practitioners who are less familiar with social theories of power. These include actor-centered, institutional, structural, and, discursive/governmental power. To complement these more common framings of power, we also discuss further approaches, notably non-human and Indigenous perspectives. We illustrate how power operates at different scales and in different contexts, and provide six guiding principles for better consideration of power in conservation research and practice. These include: (1) considering scales and spaces in decision-making, (2) clarifying underlying values and assumptions of actions, (3) recognizing conflicts as manifestations of power dynamics, (4) analyzing who wins and loses in conservation, (5) accounting for power relations in participatory schemes, and, (6) assessing the right to intervene and the consequences of interventions. We hope that a deeper engagement with social theories of power can make conservation and environmental management more effective and just while also improving transdisciplinary research and practice.